An Operational Framework to Study Diagnostic Errors in Emergency Departments: Findings From A Consensus Panel. Issue 8 (December 2021) - Mahajan, Prashant; Mollen, Cynthia; Alpern, Elizabeth R.; Baird-Cox, Kelly; Boothman, Richard C.; Chamberlain, James M.; Cosby, Karen; Epstein, Helene M.; Gegenheimer-Holmes, Jennifer; Gerardi, Michael; Giardina, Traber D.; Patel, Vimla L.; et al.
Abstract : Objective: To create an operational definition and framework to study diagnostic error in the emergency department setting. Methods: We convened a 17-member multidisciplinary panel with expertise in general and pediatric emergency medicine, nursing, patient safety, informatics, cognitive psychology, social sciences, human factors, and risk management and a patient/caregiver advocate. We used a modified nominal group technique to develop a shared understanding to operationally define diagnostic errors in emergency care and modify the National Academies of Sciences, Engineering, and Medicine's conceptual process framework to this setting. Results: The expert panel defined diagnostic errors as "a divergence from evidence-based processes that increases the risk of poor outcomes despite the availability of sufficient information to provide a timely and accurate explanation of the patient's health problem(s)." Diagnostic processes include tasks related to ( a ) acuity recognition, information and synthesis, evaluation coordination, and ( b ) communication with patients/caregivers and other diagnostic team members. The expert panel also modified the National Academies of Sciences, Engineering, and Medicine's diagnostic process framework to incorporate influence of mode of arrival, triage level, and interventions during emergency care and underscored the importance of outcome feedback to emergency department providers to promote learning and improvement related to diagnosis. Conclusions: The proposed operational definition and modified diagnostic process framework can potentially inform the development of measurement tools and strategies to study the epidemiology and interventions to improve emergency care diagnosis.